Gastro-entero-pancreatic neuroendocrine tumors in multiple endocrine neoplasia type 1: a therapy update. (March 2017) - Tonelli, Francesco; Marini, Francesca; Giusti, Francesca; Brandi, Maria Luisa
Gastro-entero-pancreatic neuroendocrine tumors (GEP-NETs) are the second most common tumors in multiple endocrine neoplasia type 1 (MEN1), mainly occurring in pancreatic islets and duodenum, usually as multiple tumors. They can manifest as both nonfunctioning and functioning tumors. Currently, surgical removal of GEP-NETs in MEN1 represents the gold standard curative approach. Conventional medical therapies for sporadic GEP-NETs showed to be effective also in a percentage of MEN1 patients. Innovative medical therapies, that have demonstrated to be effective on sporadic GEP-NETs, still need to be evaluated on MEN1 patients in prospective clinical trials and long-term follow-up. This review resumes current knowledge of MEN1 GEP-NETs, discussing surgical and medical approaches, genetic and molecular bases of tumorigenesis, and presenting novel possible drug therapies.